FAKTORFAKTOR YANG BERHUBUNGAN DENGAN FUNGSI KOGNITIF PADA PASIEN GAGAL GINJAL TERMINAL YANG MENJALANI HEMODIALISIS - Sritin Melati,* Paulus Anam Ong,* Djadjang Suhana,*Rubin Surachno Gondodiputro** (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION THE PREVALENCE OF COGNITIVE IMPAIRMENT IN ENDSTAGE RENAL DISEASE ESRD IS VERY HIGH 80 MODIFIABLE FACTORS WORSENING COGNITIVE FUNCTIONS INCLUDE DIRECT EFFECT OF AZOTEMIA INCREASED OF UREUM AND CREATININE LEVELS COMPLICATIONS OF HEMODIALYSIS TREATMENT INTRADIALYTIC HYPOTENSIONIDH AND DISEQUILIBRIUM SYNDROMEDS COMORBIDITIES OF ESRD ANAEMIA HYPOALBUMINEMIA AND VASCULAR RISK FACTORS OF ESRD HYPERTENSION DYSLIPIDEMIA DIABETES MELLITUS